Oyster size and weight measurements used for the development of weight-to-weight transformation factors and weight estimation models - Santiago E A Pineda-Metz; Verena Merk; Bernadette Pogoda (PANGAEA, 2022)
The dataset includes oyster size and weight measurements used for calculating weight-to-weight transformation factors for oyster total, shell and soft tissue wet weight to dry weight (n = 30), developing a set of allometric and random forest models to estimate oyster total (n = 1241), shell (n = 240) and soft tissue (n = 120) wet weights. For the random forest models, the additional variables location and type (if oysters were single or clustered) were also considered. The size variables were shell Height (H, umbo hinge to longest edge), Length (L, longest distance across the valve) and Width (Wi, maximum distance between external surfaces of the umbo), these were all measured in mm to the closest 0.01 mm using a digital caliper. Oysters were collected and measured at the Nature conservation area Helgoländer Felssockel, Natura 2000 site Borkum Reef Ground, and offshore wind farm Meerwind Süd I Ost. The allometric models and transformation factors allow for the reuse of data, as well as estimation of further ecological parameters and indices. Furthermore, these models and transformations could greatly enhance the outcome of monitoring efforts by restoration programs.